Historical and legal analysis of the National Police staffing development - Harbuziuk, K. H.; Гарбузюк, К. Г.; ORCID: http://orcid.org/0000-0002-6714-5074 (Підприємництво, господарство і право. - 2022. - № 5. - С. 24-28, 2022)
Здійснено історико-правовий аналіз становлення і розвитку кадрового забезпечення Національної поліції України. Охарактеризовано основні історичні етапи становлення та розвитку поліцейських органів на території України. Проаналізовано кожний етап еволюції поліції на землях нашої держави та виділено особливості роботи з кадрами в межах кожного з них. Розкрито специфіку розвитку кадрового забезпечення правоохоронців на сучасному історичному етапі. Констатовано загальну незавершеність становлення механізмів кадрового забезпечення в органах Національної поліції України. Зазначено, що проведені масштабні реформи мали свій вплив і на питання кадрового забезпечення поліцейських органів. Зокрема, вони створили передумови для формування засад єдиної кадрової політики, а також кваліфікаційних вимог до кадрів поліції. Наголошено, що, незважаючи на досить довгий історичний шлях становлення кадрового забезпечення Національної поліції України, даний процес все ще знаходиться на активній стадії свого розвитку.

The purpose of the article is to implement historical and legal analysis of the formation and development of the staffing of the National Police of Ukraine. The article, relying on the review of scientific perspectives, describes the main historical stages of the formation and development of police bodies in the territory of Ukraine. The article analyses each stage of evolution of the police in the territory of our State and highlights specificities of work with personnel within each of them. It reveals specifics of development of the staffing of law enforcers at the modern historical stage. It is established that development of mechanisms for staffing the bodies of the National Police of Ukraine is generally incomplete. It is underlined that significant reforms have had an additional impact on the staffing of the police. For example, they have created the conditions for the formation of the principles of unified personnel policy, as well as qualification requirements for the police staff. Candidates for the police rank had the following requirements: to have Russian citizenship; to be at least 25 years old; “to have good physical health” (to have a strong physique, good eyesight and hearing, to observe a sober lifestyle). In addition, it was necessary to have a certificate of past military or public service. There were certain religious restrictions. It is concluded that, despite a rather long historical path in the development of the staffing of the National Police of Ukraine, this process is still at an active stage of its evolution. For example, in 2015, a new law enforcement body – the National Police – was established in the territory of Ukraine as a radically new replacement of the militia, which existed for almost a century. The National Police has taken into account the most positive achievements in supporting and ensuring the performance of the law enforcement sector of our State. However, the reforms require the formulation of new approaches to managing police personnel and hence, the development of the staffing of this body is part of the next historical stage of evolution in which this issue is extremely relevant not only from the historical perspective, but also from the perspective of functional and legal specificities.

Проведен историко-правовой анализ становления и развития кадрового обеспечения Национальной полиции Украины. Охарактеризованы основные исторические этапы становления и развития полицейских органов на территории Украины. Проанализирован каждый этап эволюции полиции на землях нашего государства и выделены особенности работы с кадрами в пределах каждого из них. Раскрыта специфика развития кадрового обеспечения правоохранителей на современном историческом этапе. Констатирована общая незавершенность становления механизмов кадрового обеспечения в органах Национальной полиции Украины. Отмечено, что проведенные масштабные реформы оказали свое влияние и на вопросы кадрового обеспечения полицейских органов. В частности, они создали предпосылки для формирования основ единой кадровой политики, а также квалификационных требований к кадрам полиции. Отмечено, что, несмотря на достаточно длинный исторический путь становления кадрового обеспечения Национальной полиции Украины, этот процесс все еще находится на активной стадии своего развития.
Історико-правовий аналіз становлення кадрового забезпечення органів Національної поліції України
Harbuziuk, K. Historical and legal analysis of the National Police staffing development / Kostiantyn Harbuziuk // Підприємництво, господарство і право. - 2022. - № 5. - С. 24-28. -DOI: https://doi.org/10.32849/2663-5313/2022.5.04.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Історія. History. История; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; кадрове забезпечення; personnel support; кадровое обеспечение; історичні етапи; historical stages; исторические этапы